Bharajaka Pitta in Ayurveda and Contemporary Science - Arvind Kumar; Indumati Sharma; Ankita; Tulsi kapadia (AYUSHDHARA, 2024)
Ayurveda's fundamental idea is known as Tridosha. Vata, Pitta and Kapha are the body's three pillars. One of the three, Pitta is in charge of all bodily transformations, including hormonal and metabolic processes. The fire is referred to as “Pitta” The term "Tapa santapaiti" refers to Pitta, which is that which generates heat and a burning sensation. It offers perception of vision, concerning healthy digestion, preservation of body temperature, appropriate skin tone and the promotion of intelligence, self-assurance and bravery. Pachaka, Ranjaka, Sadhaka, Alochaka, and Bhrajaka are the five different varieties of Pitta. Bhrajaka Pitta is in charge of keeping the body temperature stable as well as providing the skin its colour and shine. Bhrajaka Pitta causes various drugs, Abhyanga (oil massage), Parisheka (hot water or oil pouring), Avgaha (tub bath), and Lepa (paste) to be absorbed and digested. This page explains how Bhrajka Pitta's physiological activity relates to current medical knowledge. To enhance comprehension of the notion and enable comparison with current scientific research, the fundamental materials for this study were gathered from old Ayurvedic texts and their available commentary, in addition to modern medical science textbooks.